MULTIDIMENSIONAL HYBRID BOUNDARY VALUE PROBLEM - Marzena Szajewska (Acta Polytechnica, 2018)
The purpose of this paper is to discuss three types of boundary conditions for few families of special functions orthogonal on the fundamental region. Boundary value problems are considered on a simplex F in the real Euclidean space Rn of dimension n > 2.